Usefulness of Proton and Phosphorus MR Spectroscopic Imaging for Early Diagnosis of Parkinson's Disease. Issue 1 (10th December 2013) - Weiduschat, Nora; Mao, Xiangling; Beal, M. Flint; Nirenberg, Melissa J.; Shungu, Dikoma C.; Henchcliffe, Claire
ABSTRACT BACKGROUND AND PURPOSE Cerebral mitochondrial dysfunction has been observed in Parkinson's disease (PD). If mitochondrial dysfunction is an early event contributing to PD development, then noninvasive techniques that detect disturbed energy metabolism in vivo might be useful tools for early diagnosis and treatment monitoring. In the present study, we tested the hypothesis that proton (1H) and phosphorus (31P) magnetic resonance spectroscopy (MRS) measures of brain metabolites are able to differentiate between individuals with early PD and healthy volunteers (HVs). METHODS During this cross‐sectional study including 20 subjects with early PD and 15 age‐matched HV, ventricular lactate (anaerobic glycolysis); and regional levels of N‐acetylaspartate (neuronal integrity); choline (membrane turnover); creatine (energy metabolism); ATP and other phosphate‐containing compounds (oxidative phosphorylation) were determined using brain 1H and 31P MRS. RESULTS No metabolic abnormalities were detectable in early‐stage PD patients. Metabolite concentrations were not related to age, disease duration, or Unified Parkinson's Disease Rating Scale motor scores. DISCUSSION In early PD, neither 1H nor 31P MRS were able to detect metabolic abnormalities, a finding that is in contrast to published data in more advanced PD cohorts. MRS under dynamic conditions might uncover latent energy deficits in early PD, thus warranting future study.